2019
DOI: 10.3174/ajnr.a6210
|View full text |Cite
|
Sign up to set email alerts
|

Empty Sella Is a Sign of Symptomatic Lateral Sinus Stenosis and Not Intracranial Hypertension

Abstract: BACKGROUND AND PURPOSE: Empty sella has been reported in patients with idiopathic intracranial hypertension and is thought to be a sign of elevation of intracranial pressure. However, it can also be found in patients with lateral sinus stenosis presenting with isolated pulsatile tinnitus without signs of intracranial hypertension. We hypothesized that the volume of the sella turcica would be similar in both groups of patients undergoing stent placement for lateral sinus stenosis. MATERIALS AND METHODS: Consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…1,5,25,26 In comparison with previous series of spontaneous CSF leaks, our study showed similar results concerning the age of the patients, sex ratio, rates of obesity, and empty sella. 11,19,24 Of note, the low rate of papilledema and elevated CSF pressure were also in accordance with previous reports. 26 In comparison with an IIH series, our study confirmed that patients with CSF leaks were older (45-65 years vs 25-36 years) and had fewer clinical signs of IIH (in particular, headaches reported in 0-7% vs 75-94%) but had a similar degree of empty sella.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…1,5,25,26 In comparison with previous series of spontaneous CSF leaks, our study showed similar results concerning the age of the patients, sex ratio, rates of obesity, and empty sella. 11,19,24 Of note, the low rate of papilledema and elevated CSF pressure were also in accordance with previous reports. 26 In comparison with an IIH series, our study confirmed that patients with CSF leaks were older (45-65 years vs 25-36 years) and had fewer clinical signs of IIH (in particular, headaches reported in 0-7% vs 75-94%) but had a similar degree of empty sella.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison with previous series of spontaneous CSF leaks, our study showed similar results concerning the age of the patients, sex ratio, rates of obesity, and empty sella 11,19,24 . Of note, the low rate of papilledema and elevated CSF pressure were also in accordance with previous reports 26 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Zetchi et al. 24 demonstrated that the appearance of an empty sella in patients with lateral sinus stenosis, was similar whether the patients had established IIH or isolated PT and hypothesized that this is result of disruption of CSF flow, but not necessarily due to increased intracranial pressure. The authors acknowledge the fact that a lumbar puncture was not performed in the isolated pulsatile tinnitus group and it is possible that some patients in this group had unrecognized intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%